Analisis Butir Soal Biologi Kelas XI Madrasah Aliyah Sakinah Kerinci Menggunakan Program Komputer Anates 4.0 For Windows - Fietri, Winda Ayu; Zulyusri, Zulyusri; Violita, Violita (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to find out the quality of the details of biology class XI MAS Kerinci about the excretory system by using the program anates version 4. This research uses descriptive quantitative approach and data collection techniques conducted with test techniques in the form of questions about the excretory system amounting to 40 points in the form of multiple choice. The population in this study was all students of grade XI MAS Kerinci as many as 40 students. The sample in this study as many as 36 students determined through the formula Slovin with a level of significance of 5%. Data analysis using computer program Anates version 4 for windows. The results showed a very high problem reliability rate of 0.90, good differentiating power of 47.5%, medium difficulty rate of 90%, and excellent pengecoh quality of 100%.Â